New microcogeneration with solar energy: stirling, thermal and photovoltaic systems. - Auñón-Hidalgo, Juan Antonio; Sidrach-de-Cardona-Ortin, Mariano; Marfil, M.; Gómez de la Varga, J. (International Conference on Renewable Energies and Power Quality (ICREPQ’18), 2018)
This paper analyses the viability of a new microcogeneration system with a Stirling engine-based micro-CHP (combined heat and power) and renewable solar energy: thermal and photovoltaic system in order to supply the energy demand of an isolated home. The right sizing of solar energy systems should allow optimizing both the available solar resources and gas consumption for one specific climatological conditions. The present work shows the first results of the experimental study of a micro-cogeneration system (micro-CHP based on the Stirling motor) supported with renewable energy. The system of self-government covers the theoretical daily consumption of a house. In this results, the different contributions of the subsystems to the daily thermal and electric demand are displayed.
https://www.icrepq.com/full-papers.htm --- he papers presented at the ICREPQ'24 could bepublished, free of charge, in the open access "Renewable Energies and Power Quality Journal (RE&PQJ)", ISSN: 2172-038X
Keywords: Motores; Ingeniería eléctrica; Microcogeneration; Pv System; Stirling engine